The Argument from Evil, The Argument from Hiddenness, and Supernaturalistic Alternatives to Theism - Lataster, Raphael (Religions, 2022)
In this brief article, I consider James Sterba’s logical argument from evil, finding it to be ultimately unsuccessful. Not for the various issues Sterba raises, which do seem to be problematic if God exists, but for the logical approach itself. I encourage Sterba to shift tack, to embrace the evidential argument from evil, which is not at all concessionary, as he seems to think, and is an extremely powerful argument against the probability of theism, especially when we open the debate to the supernaturalistic alternatives to theism. I also encourage Sterba to reconsider his dismissive attitude towards the argument from hiddenness, which, in its evidential form, is also a very powerful argument against God’s existence, either employed independently or incorporated into the argument from evil.